2016
DOI: 10.1002/lsm.22562
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated Er:YAG laser versus fully ablative Er:YAG laser for scar revision: Results of a split scar, double blinded, prospective trial

Abstract: Although this study is limited by a short follow-up period, it shows a statistically significant superior outcome in fractionated Er:YAG over fully ablative Er:YAG for scar revision. It also adds quantitative values to the assessment of scar appearance when treated with fractionated lasers compared to fully ablative lasers. It was also found that the fractionated Er:YAG had increased patient satisfaction, but there was no difference in reported pain scores. These data are useful when counseling patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…The clinical trials demonstrated a significant improvement in scar appearance . Due to decreased erythema and pruritus , multiple laser wavelengths have been used to manage scars, including argon (514 nm), pulsed dye laser (595 nm), Nd:YAG (1064 nm), Er: YAG, and carbon dioxide (10.6 μm) . The 595 nm pulsed dye laser is commonly used for the HTS treatment due to low risk of side effects and complications .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical trials demonstrated a significant improvement in scar appearance . Due to decreased erythema and pruritus , multiple laser wavelengths have been used to manage scars, including argon (514 nm), pulsed dye laser (595 nm), Nd:YAG (1064 nm), Er: YAG, and carbon dioxide (10.6 μm) . The 595 nm pulsed dye laser is commonly used for the HTS treatment due to low risk of side effects and complications .…”
Section: Introductionmentioning
confidence: 99%
“…Ablative fractional laser treatment improves the quality and appearance of skin and scars , but offers minor improvement in skin laxity compared with surgical excision and lifting operations, even when a comparable amount of skin has been removed. Ablative fractional laser treatment provides a potent stimulus for skin remodeling, but is conceptually equivalent to leaving thousands of small open wounds without primary closure.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional laser therapy with either non-ablative or fully ablative lasers has been shown to improve the color, texture, thickness and patient satisfaction of atrophic surgical scars [31][32][33] . These lasers are effective because they stimulate neocollagenesis and dermal remodeling.…”
Section: Atrophic Scarsmentioning
confidence: 99%